Examining the Influence Facility Managers exert within the Urban Domain: A case study of the Cape Metropole area - Buerger, Renee (Department of Construction Economics and Management, 2024)
Examining the influence facility managers have in the urban domain is the focus of this research. Facility managers are custodians of the largest collective asset base within cities. Facility managers' daily operations, such as maintenance, cleaning, gardening, beautification, parking, and security, could ensure not only preservation of the urban precinct but improvement thereof and minimise wastage. The researcher applied rigorous analytics on data garnered from the small purposive sample by means of unstructured interviews. The study engaged a variety of respected, and qualified built environment stakeholders active in the Cape Metropolitan Area to examine their lived reality. Facility managers, as a collective, have an influence in the greater urban domain, and could, as a collective, add significantly to property values and land value capture. This, in turn, can secure a greater revenue stream for municipalities, providing funding for improved service delivery in a cyclical fashion. Not only for the Cape Metropole Area (CMA), but potentially for increasing city populations globally, to meet the predicted demand to accommodate 70% of the worlds' population by 2025. Urban facilities management - not clearly defined nor adequately resourced may benefit from facility managers' expertise. They could be best positioned to fill professional roles as urban facilities managers to maintain and improve public precincts and the relevant infrastructure. A minor shift in the collective mindset of a large group of facility managers could be the key to urban sustainability. To examine the subject and answer the research question, a grounded theory method, using unstructured interviews, and an inductive analysis of the data gleaned performed. In the main, findings drawn from the interviews with various built environment professionals, echoed the fact that facility managers do have an influence, and could improve the urban domain. Participants considered facility managers' actions as enablers of safe, improved, sustainable and salubrious precincts which could bring about land value capture. The research discusses the validation of the findings and the substantive theory, adding to the body of knowledge that underpins sustainable urban facilities management. It concludes with recommendations for further similar studies which could deliver a formal theory. Furthermore, the study suggests that the development of policy, legislation, and regulation, may enable organisations to deploy resources to benefit urban facilities management. Finally, recommending transferring the experience of facility managers' skills to inexperienced facility managers by way of mentoring or formal academic tutoring is recommended. This could improve precincts for all walks of life.